2016
DOI: 10.1007/s10096-016-2681-1
|View full text |Cite
|
Sign up to set email alerts
|

Colistin combination therapy improves microbiologic cure in critically ill patients with multi-drug resistant gram-negative pneumonia

Abstract: Currently, in vitro synergy with colistin has not translated into improved clinical outcomes. This study aimed to compare colistin combination therapy to colistin monotherapy in critically ill patients with multi-drug resistant gram-negative (MDR-GN) pneumonia. This was a retrospective analysis of critically ill adult patients receiving intravenous colistin for MDR-GN pneumonia comparing colistin combination therapy to colistin monotherapy with a primary endpoint of clinical cure. Combination therapy was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However they claimed that such effectiveness should be further explored in vivo to be considered for clinical use (Lagerbäck et al, 2016). Parchem et al (2016) confirmed that colistin combination therapy should be considered in critically ill patients with MDR Gram-negative pneumonia.…”
Section: Clinical Use and Indications Of Colistin In Pig Productionmentioning
confidence: 71%
“…However they claimed that such effectiveness should be further explored in vivo to be considered for clinical use (Lagerbäck et al, 2016). Parchem et al (2016) confirmed that colistin combination therapy should be considered in critically ill patients with MDR Gram-negative pneumonia.…”
Section: Clinical Use and Indications Of Colistin In Pig Productionmentioning
confidence: 71%
“…Addressed infections ranged from pneumonia (n = 10 studies) 716 , blood stream infections (n = 15 studies) 1731 , osteoarticular infections (n = 1 study) 32 , and studies comprising mixed forms of infections (n = 27 studies) 3359 . Two of the included studies were RCTs 36,43 , six case-control studies 7,9,15,17,53,55 and forty-five case series/cohort studies 8,1014,16,1835,3742,4452,54,5659 . The studies included a total of 4514 patients: 41% of patients (n = 1848) were treated with monotherapy, 59% (n = 2666) with combination therapy.
Figure 1Study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Combination antibiotic therapy has been associated with improved clinical and microbiological outcomes when treating KPC Enterobacteriaceae in patients with pneumonia and severe sepsis [85][86][87][88][89]. However, robust prospective clinical trial data have been limited, with recommendations based on retrospective series with significant clinical heterogeneity.…”
Section: Combination Antimicrobial Therapy For Cre Infectionsmentioning
confidence: 99%